FAKTOR-FAKTOR YANG TERKAIT DENGAN PENGENDALIAN SISTEM MANAJEMEN INFORMASI DAN ADMINISTRASI TERPADU DI RSUD SIDIKALANG TAHUN 2019 - Rizka Annisa; Diana Sinulingga; Elisabeth Dame Manalu (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
This study aims to analyze related factors based on technology, human, organizational, and benefit variables with the Inhibitors of Management Information Systems and Integrated Administration Management at Sidikalang Hospital in 2021. The population of this study were Sidikalang Hospital officers in the outpatient, inpatient, Medical records, and SIMRS officers as many as 35 respondents. The method used in this study was analyzed by means of the Chi-Square correlation test. The results of the research on the technology variable showed that the majority said it was good as many as 32 people (91.4%). For the human factor, the majority stated that it was good as many as 27 people (77.1%). For organizational factors, the majority said it was good as many as 24 people (68.6%). the majority of the benefit factors stated that they were good as many as 20 people (57.1%). So it can be concluded that there is a relationship between technological factors, human factors, organizational factors and benefit factors with the Inhibitors of Integrated Management Information Systems and Administration Management at Sidikalang Hospital in 2021.